A longitudinal study of socioeconomic status, family processes, and child adjustment from preschool until early elementary school: the role of social competence - Rikuya Hosokawa; Toshiki Katsura (BMC, 2017)
Abstract Objective Using a short-term longitudinal design, this study examined the concurrent and longitudinal relationships among familial socioeconomic status (SES; i.e., family income and maternal and paternal education levels), marital conflict (i.e., constructive and destructive marital conflict), parenting practices (i.e., positive and negative parenting practices), child social competence (i.e., social skills), and child behavioral adjustment (i.e., internalizing and externalizing problems) in a comprehensive model. Methods The sample included a total of 1604 preschoolers aged 5 years at Time 1 and first graders aged 6 years at Time 2 (51.5% male). Parents completed a self-reported questionnaire regarding their SES, marital conflict, parenting practices, and their children's behavioral adjustment. Teachers also evaluated the children's social competence. Results The path analysis results revealed that Time 1 family income and maternal and paternal education levels were respectively related to Time 1 social skills and Time 2 internalizing and externalizing problems, both directly and indirectly, through their influence on destructive and constructive marital conflict, as well as negative and positive parenting practices. Notably, after controlling for Time 1 behavioral problems as mediating mechanisms in the link between family factors (i.e., SES, marital conflict, and parenting practices) and behavioral adjustment, Time 1 social skills significantly and inversely influenced both the internalization and externalization of problems at Time 2. Conclusions The merit of examining SES, marital conflict, and parenting practices as multidimensional constructs is discussed in relation to an understanding of processes and pathways within families that affect child mental health functioning. The results suggest social competence, which is influenced by the multidimensional constructs of family factors, may prove protective in reducing the risk of child maladjustment, especially for children who are socioeconomically disadvantaged.